DISTRIBUTION OF POLYMORPHIC VARIANTS OF THE CYP1A1 AND CYP1A2 GENES IN THE MONGOLOID AND CAUCASOID POPULATION OF THE SOUTH OF KUZBASS - Лузина, Фаина Анисимовна; Дорошилова, Анастасия Викторовна; Казицкая, Анастасия Сергеевна; Гуляева, Ольга Николаевна; Ядыкина, Татьяна Константиновна; Жукова, Анна Геннадьевна (Medicine in Kuzbass, 2021)
The subject of the study was the frequency of occurrence of polymorphic variants of the CYP1A1 and CYP1A2 genes in the indigenous (Shor) and alien (Caucasoid) population of the Kemerovo region.The objective was to study the frequency of occurrence of polymorphic variants of the CYP1A1 (rs4646903) and CYP1A2 (rs762551) genes in the indigenous (Shor) and alien (Caucasoid) population of the Kemerovo region to identify the specifics in their distribution among different ethnic groups.Methods. For genetic studies, venous blood was taken from the indigenous (245 Shors) and alien (48 Russians) population of Gornaya Shoria and in the population of Novokuznetsk (471 individuals). DNA samples were isolated by phenol-chloroform extraction. The polymorphism of the CYP1A1 and CYP1A2 genes was studied by real-time PCR.Main results. Statistically significant differences in the distribution of polymorphic variants of the CYP1A1 and CYP1A2 genes in the indigenous and alien Caucasoid population of the South of Kuzbass were revealed. It was shown that the relatively rare genotype GG of the CYP1A1 gene was found in Shors 3.5 times more often than in Caucasoids, and the frequency of occurrence of the relatively rare genotype CC of the CYP1A2 gene was also 1.5 times higher in Shors in comparison with the Caucasoid population of Gornaya Shoria. The frequency of the mutant allele G of the CYP1A1 gene and the «wild» allele C of the CYP1A2 gene in Shors also exceeded the similar frequencies in Caucasoids by 3.48 and 1.09 times, respectively.Conclusion. The obtained data can be used in planning and conducting genetic and epidemiological investigations, studying the associations of these markers with multifactorial diseases and calculating the possible individual and population risk, as well as for developing preventive measures to preserve the health of the population, taking into account the ethno-genetic specifics of the region.
Keywords: CYP1A1 genes; CYP1A2 genes; genotypes; alleles; Shors; Caucasoids